Change of religion by a spouse as a culpable cause of the breakdown of marital life. A constitutional-law perspective (Discourse of Law and Administration, 2024)
According to the jurisprudence of Polish courts, including the Supreme Court, a spouse who, as a result of their changing of religious affiliation, changes some of the rules of family life, as well as takes educational measures aimed at instilling the principles of their newly adopted religion into joint minor children, commits a breach of the duty of marital fidelity, which in turn justifies the attribution to him or her the guilt for the breakdown of the marriage. The above position raises serious constitutional doubts. First of all, the courts made the possibility for a spouse to exercise his or her freedom of religion dependent on the reaction (consent or indifference) of the other spouse, thus disregarding its inalienable nature. Indeed, the conclusion of marriage entails only such limitations on the rights and freedoms of the individual as are necessary for the realisation of the functions of marriage arising from its essence. It does not therefore have the effect of relinquishing by the spouses of the exercise of their freedom of religion. Furthermore, the courts failed to strike a proper balance between the constitutional right of both parents to raise their children in accordance with their respective beliefs. They also failed to examine the position of the children themselves on their religious upbringing in a situation of conflict between the parents, thus failing to take into account their degree of maturity and their freedom of conscience and religion. The adoption of a constitutional perspective by the courts in this type of cases would not only result in a ruling that is in line with the provisions and axiology of the Constitution, but would also contribute to the fuller realisation of substantive justice.
Keywords: change of religion; fault for the breakdown of marital life; duty of marital fidelity; religious; upbringing of children; limitations of freedom to manifest one’s religious beliefs